First Report of Pestalotiopsis clavispora (G.F. Atk.) Steyaert Causing Crown Rot Disease on Strawberry in India - D. A. Bhagariya; V. P. Prajapati (International Journal of Economic Plants)
The crown rot disease was recorded for the first time on strawberry Field from Hill Millet Research Station, Waghai, Gujarat state of India during 2017-2018. The diseased plants showed drying from the edge of the leaves. Dark lesion appears first on leaves and spreads downward to the crown region. The severely infected plant parts i.e., leaves, flowers, stems, fruits and roots are gradually turned into dark black in colour and  later on plant had completely dried and resemble the symptoms of crown rot. The fungus was isolated from the diseased plant parts and subsequent re-inoculation of the same to healthy plants and its pathogenicity confirmed which revealed that Pestalotiopsis clavispora (G.F. Atk.) Steyaert is the causal organism. Pathogenicity tests showed that Pestalotiopsis clavispora could infect strawberry, which developed the same symptoms under artificial inoculation conditions to that observed in the field. Further,  the fungus was identified based on morphological and cultural characteristics and this is the first report from India showing that Pestalotiopsis clavispora causes crown rot on strawberry.